Tween 80 influences the production of intracellular lipase by Schizochytrium S31 in a stirred tank reactor. (February 2017) - Byreddy, Avinesh R.; Rao, Nalam Madhusudhana; Barrow, Colin J.; Puri, Munish
Graphical abstract: Highlights: Tween 80 influenced lipase productivity in Schizochytrium S31. Sonication was optimised for the extraction of intracellular lipase from Schizochytrium S31. Fatty acid chain length selectivity of crude lipase was evaluated using p -NP esters. The extracted lipase showed preferential hydrolysis of DHA over EPA. Abstract: Marine microorganisms are a potential source of enzymes with structural stability, high activity at low temperature and unique substrate selectivity. Thraustochytrids are marine heterotrophic microbes, well known for the production of omega-3 fatty acids. In this study the effect of Tween 80 as a carbon source was investigated with regard to biomass, lipase and lipid productivity in Schizochytrium sp. S31. Tween 80 (1%) and 120 h of incubation were the optimum condition period for biomass, lipid and lipase productivity in a stirred tank reactor. The yields obtained were 0.9 g L −1 of biomass, 300 mg g −1 of lipid and 39 U/g of lipase activity. Sonication was optimised in terms of time and acoustic power to maximise the yield of extracted lipase. The extracted lipase from Schizochytrium S31 was observed to hydrolyse long chain polyunsaturated fatty acids DHA and EPA.